Front Line Surgery A Practical Approach - Martin, MD, FACS, Matthew J.; Martin, MD, FACS, Matthew J.; Beekley, MD, FACS, Alec C.; Beekley, MD, FACS, Alec C. (Springer New York : Imprint: Springer, 2011)
Front Line Surgery is designed to provide practical insights for surgeons whose areas of practice demand quick best-outcome based solutions to complex and urgent clinical problems. Both editors are active duty officers and surgeons with multiple tours in Iraq. Each chapter provides detailed instructions and combat/emergency surgical principles with multiple detailed illustrations. While the focus is clearly clinical, the authors also provide clinical pearls in both traditional and non-traditional narrative. Top Ten Combat Trauma Lessons 1. Patients die in the ER, and 2. Patients die in the CT scanner; 3. Therefore, a hypotensive trauma patient belongs in the operating room ASAP. 4. Most blown up or shot patients need blood products, not crystalloid. Avoid trying “hypotensive resuscitation” – it’s for civilian trauma. 5. For mangled extremities and amputations, one code red (4 PRBC + 2 FFP) per extremity, started as soon as they arrive. 6. Patients in extremis will code during rapid sequence intubation, be prepared, and intubate these patients in the OR (not in the ER) whenever possible. 7. This hospital can go from empty to full in a matter of hours; don’t be lulled by the slow periods. 8. The name of the game here is not continuity of care, it is throughput. If the ICU or wards are full, you are mission incapable. 9. MASCALs live or die by proper triage and prioritization – starting at the door and including which x-rays to get, labs, and disposition. 10. No Personal Projects!!! They clog the system, waste resources, and anger others. See #8 above. Reprinted from "The Volume of Experience (January 2008 edition)", a document written and continuously updated by U.S. Army trauma surgeons working at the Ibn Sina Hospital, Baghdad, Iraq.